THE CENSORS’ INFLUENCE ON MARRIAGE IN REPUBLICAN ROME - Tarwacka, Anna (Zeszyty Prawnicze, 2018)
The office of censor was one of the institutions guaranteeing the stability of the socio-political system of Republican Rome. The censors supervised public morality and promoted population growth. In this connection they encouraged citizens to contract marriage and raise children. Their chief instruments of pressure were the orations they made during the contiones. But sometimes they resorted to more stringent measures, such as administering a censorial note or granting rewards to men who fathered many oﬀspring.